EFFECT OF ANXIETY AND WORK FATIGUE ON JOB BURNOUT, DISTRESS, HEALTH EATING INDEX AND BLOOD PRESSURE THROUGH COPING MECHANISM IN OIL AND GAS COMPANY - Shintia Yunita Arini; Dominikus Raditya Atmaka; Irpan Nurhakim; Andian Shodiq; Devy Syanindita Roshida (The Indonesian Journal of Public Health, 2023)
Introduction: Workers in oil and gas companies are one of several groups of workers who have a heavy workload, both physically and psychologically, owing to the heavy work responsibilities related to the duration of work, which is not in accordance with the standard working time specified in Indonesia. Based on research conducted in similar industries, 69% of workers in critical jobs experience both acute and chronic fatigue.  If not managed properly, it will result in occupational burnout. Aims: of this research was to determine whether there is a relationship between coping style, eating habits, work stress, fatigue and occupational burnout Method: Design study of cross-sectional manner with the research respondents being permanent workers in oil and gas companies in Bojonegoro, East Java. The total sample comprised of 102 respondents. The data obtained will then be statistically processed using IBM SPSS software with multiple regression tests. Result: The level of work fatigue experienced by oil and gas company employees had a significant indirect effect on the healthy eating index through the copying mechanism variable, and the anxiety experienced by oil and gas company employees had a significant indirect effect on the healthy eating index and blood pressure, both systolic and systole, and diastole via the copying mechanism variable. Conclusion: Anxiety experienced by workers influences the healthy eating index and systolic blood pressure with coping mechanisms as an intervening variable. Work fatigue experienced by workers influences the healthy eating index, with coping mechanisms as an intervening variable.